A Tailored Multifunctional Anticancer Nanodelivery System for Ruthenium‐Based Photosensitizers: Tumor Microenvironment Adaption and Remodeling. Issue 1 (25th November 2019) - Liang, Jin‐Hao; Zheng, Yue; Wu, Xiao‐Wen; Tan, Cai‐Ping; Ji, Liang‐Nian; Mao, Zong‐Wan
Abstract: Ruthenium complexes are promising photosensitizers (PSs), but their clinical applications have many limitations. Here, a multifunctional nano‐platform PDA‐Pt‐CD@RuFc formed by platinum‐decorated and cyclodextrin (CD )‐modified polydopamine (PDA ) nanoparticles (NPs) loaded with a ferrocene‐appended ruthenium complex (RuFc ) is reported. The NPs can successfully deliver RuFc to the tumor sites. The release of RuFc from the NPs can be triggered by low pH, photothermal heating, and H2 O2 . The combined photodynamic and photothermal therapy (PDT‐PTT) mediated by PDA‐Pt‐CD@RuFc NPs can overcome the hypoxic environment of tumors from several aspects. First, the platinum NPs can catalyze H2 O2 to produce O2 . Second, vasodilation caused by photothermal heating can sustain the oxygen supplement. Third, PDT exerted by RuFc can also occur through the non‐oxygen‐dependent Fenton reaction. Due to the presence of PDA, platinum NPs, and RuFc, the nanosystem can be used in multimodal imaging including photothermal, photoacoustic, and computed tomography imaging. The NPs can be excited by the near‐infrared two‐photon light source. Moreover, the combined treatment can improve the tumor microenvironments to obtain an optimized combined therapeutic effect. In summary, this study presents a tumor‐microenvironment‐adaptive strategy to optimize the potential of ruthenium complexes as PSs from multiple aspects. Abstract : A multifunctional nanocomposite for ruthenium‐based photosensitizers that can successfully adapt to and remodel tumor microenvironments is developed. The release of the photosensitizer can be triggered by low pH, photothermal heating, and H2 O2 . The as‐fabricated nanoparticles can accumulate in tumor tissues and show great potential for combined therapy with multimodal imaging capacities.